The modern view of general practitioner on the problem of iron deficiency anemia in patients with cardiovascular pathology - G. N. Gorohovskaya; A. I. Martynov; V. L. Yun; M. M. Petina (Медицинский совет, 2020)
Presently, cardiovascular diseases (CVD) hold the leadership positions not only in terms of prevalence, but also in the mortality structure all over the world. The incidence of CVD increases with age and accounts for more than 50% among the population over 70 years old in Russia. As it is known, old age is characterized by polymorbidity, and all concomitant conditions change the clinical picture, course, and prognosis of CVD. Anemic syndrome is one of the aggravating factors of CVD, particularly in the case of iron deficiency. Anemia is also an important problem of health service practices, as it affects the quality of life, mortality and is a common reason for seeking medical advice. The literature analysis shows that anemia is an independent predictor of cardiovascular disease and adverse outcomes. Due to the fact that the incidence rate of anemia increases with age, it makes it a frequent concomitant pathology of cardiovascular accidents. The increase in sympathetic activity and cardiac output due to prolonged hypoxia-induced vasodilation, which results in left ventricular hypertrophy and an increase in the size of the heart and, accordingly, in the increased oxygen consumption seems to be the mechanism of the pathology. Also, decreased myocardial tolerance to low hemoglobin levels is observed in patients with coronary artery disease as compared with healthy subjects. Therefore, patients need to pass a comprehensive examination, including the mandatory measurement and monitoring of hemoglobin levels. Primary measures should be aimed at eliminating the etiological factor that causes anemia of varying severity. Oral and intravenous iron drugs, as well as erythropoietin drugs should be used as the main therapy.Despite the effective diagnosis and treatment regimens designed for the treatment of these diseases, and a wide range of effective drugs, problems in this area remain the most urgent.